Gender and geographic differences in grip strength and static balance among Special Olympics athletes - Gose, M.; Esposito, P. (International Journal of Exercise Science Conference Proceedings, 2026)
Individuals with intellectual and developmental disabilities often experience deficits in muscular strength and balance, which can impact functional independence, injury risk, and sport participation. Grip strength and balance are core components of the Special Olympics FUNfitness screening program and serve as practical indicators of overall functional health.